The optimization of development process of petrol-gas stations network with the purpose to increase energy efficiency - Larisa Jovanović; Dijana Fedjunina; Milan Radosavljević (Zaštita Materijala)
Development of petrol/gas stations network requires a complex approach to the assessment of environmental impact. The use of appropriate indicators according DPSIR methodology enables optimization of processes at oil/gas stations and increase energy efficiency. Use of renewable energy and new insulating materials has great importance to reduce energy consumption for heating of petrol/gas stations buildings. As a replacement styropor and styrodur (for added insulation of walls and floors) is much more efficient to use blocks of innovative insulating materials in the construction of new facilities. Widespread application of renewable energy and thermal insulation materials in buildings of oil/gas stations, reducing electricity consumption by using energy-saving LED technology, as well as savings in transportation fuels reducing the weight of tankers using Al alloys and composite materials are the basic methods of increasing energy efficiency. The use of Al alloys in tankers and reservoirs design conductive to increase corrosion resistance.